Drivers of Intermodal Rail Freight Growth in North America - Spychalski, John C.; Thomchick, Evelyn (European Journal of Transport and Infrastructure Research, 2009)
Intermodal rail freight service, in the form of semi-trailers and containers carried by rail in coordination with connecting road and water transport operators, emerged in North America on a few railways during the 1920s and 1930s. Experience gained from these early ventures inspired widespread introduction of intermodal service offerings after 1950. Between 1990 and 2005, rail intermodal traffic grew 87.7 percent, from 6.2 million to 11.7 containers and trailers, and now holds a significant position in the aggregate traffic base of the major North American rail freight carriers. Previous research and other sources of data and information are drawn upon to identify key drivers of this growth within the context of a conceptual model. The driving forces include changes in transport providers’ business policies and practices, government deregulation of pricing and other commercial actions by firms in rail and competing modes of transport, advancements in rail intermodal technology, and changes in supply chain management processes by shippers and consignees that have intensified demand for freight service of higher quality and lower cost. Comments on transferability to Europe of lessons learned from intermodal business experience in North America are provided in the concluding section.